2022
DOI: 10.1186/s13046-022-02298-1
|View full text |Cite
|
Sign up to set email alerts
|

FAM167A is a key molecule to induce BCR-ABL-independent TKI resistance in CML via noncanonical NF-κB signaling activation

Abstract: Background BCR-ABL-independent drug resistance is a barrier to curative treatment of chronic myeloid leukemia (CML). However, the molecular pathways underlying BCR-ABL-independent tyrosine kinase inhibitor (TKI) resistance remain unclear. Methods In silico bioinformatic analysis was performed to identify the most active transcription factor and its inducer that contribute to BCR-ABL-independent TKI resistance. Tandem mass spectrometry analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Function of the FAM167A gene located 27 kb upstream of BLK has recently been shown to be an activator of the non-canonical activation pathway of NFκB, which is potentially important for mechanisms of the inflammatory phenotypes with genetic associations at this locus ( Mentlein et al, 2018 ; Yang et al, 2022 ). We, therefore, retain FAM167A as an SLE candidate gene, acknowledging the existing circumstantial evidence supporting BLK as a participant in the mechanism altering disease risk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Function of the FAM167A gene located 27 kb upstream of BLK has recently been shown to be an activator of the non-canonical activation pathway of NFκB, which is potentially important for mechanisms of the inflammatory phenotypes with genetic associations at this locus ( Mentlein et al, 2018 ; Yang et al, 2022 ). We, therefore, retain FAM167A as an SLE candidate gene, acknowledging the existing circumstantial evidence supporting BLK as a participant in the mechanism altering disease risk.…”
Section: Resultsmentioning
confidence: 99%
“…DIORA-1 is a disordered protein ( Mentlein et al, 2018 ) that is secreted and binds desmoglein-1 (DSG1) to gain cell entry, which then activates NFκB via its non-canonical pathway by liberating NFκB-inhibitor kinase from DSG1. DIORA-1 appears responsible for much BCR-ABL-tyrosine kinase inhibitor resistance in chronic myelogenous leukemia (CML) ( Yang et al, 2022 ). Certainly, DIORA-1 has functional properties that make the level of activity of this gene product attractive for mediating SLE risk.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, miRDB and TargetScan predicted FAM167A as the target gene of miR-29a-3p. FAM167A is found in some leukemias and lymphomas and is typically associated with a poor prognosis [44].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that exosomal miR-29a-3p in the SD internal environment promotes the metastasis of HCC via activation of the FAM167A-α1integrin-NF-κB signaling pathway. It has been reported [44], that the FAM167A gene can activate the NF-κB pathway and induce BCR-ABL-independent tyrosine kinase inhibitor resistance. The FAM167A protein activates the non-canonical NF-κB pathway by binding to desmoglein-1 (DSG1), a cell adhesion protein.…”
Section: Discussionmentioning
confidence: 99%
“…Recent additions to the differentially expressed genes which may serve as potential biomarkers of progression or TKI resistance include downregulation of the large HECT E3 ubiquitin ligase HERC1 in leukemic cells [57], FAM167A induced activation of the noncanonical NF-κB pathway in TKI-resistant CML cells [58], and upregulation of exosomal proteins RPL13 and RPL14 in the plasma of imatinib resistant patients [59]. Additionally, the MS4A3 transmembrane protein is downregulated in CML progenitor cells preventing differentiation [60].…”
Section: Altered Gene Expression and Epigenetic Changesmentioning
confidence: 99%